Corporate Governance: International literature evidence - Fatima Adel Dakel (Al-Qanṭara, 2022)
Abstract This research is a review of the literature on corporate governance. Its goal is to consolidate our knowledge in this field, examine its evolution, and suggest future research directions. We discovered that the empirical results for many of the governance mechanisms studied are mixed in our review of the past and current literature on various governance measures and their effect on firm performance. We propose that the mixed results are due to the application of a "one size fits all" set of governance measures, which is ineffective for all types of firms due to organisational complexity and differences in ownership structures. As a result, we investigate more technologically advanced methodologies, such as machine learning. We believe that this line of research could not only improve but also transform.